Prime ideal on the end_Z (Z^n ) Ring - Ikhtiyar, Zakaria Bani; Puspita, Nikken Prima; Udjiani, Titi (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
The set of all endomorphisms over -module  is a non-empty set denoted by . From  we can construct the ring of  over addition and composition function. The prime ideal is an ideal which satisfies the properties like the prime numbers. In this paper, we take the ring of integer number  and the module of  over  such that the  is a ring. Furthermore, we show the existences of prime ideal on the . We also applied a prime ideal property to prime ideal on   .